2021
DOI: 10.1002/ejoc.202100415
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Exploration of Abscisic Acid Receptor Agonists Against Dought Stress by Adding Constraint to a Tetrahydroquinoline‐Based Lead Structure

Abstract: New oxotetrahydroquinolinyl-and oxindolinyl sulfonamides interacting with RCAR/(PYR/PYL) receptor proteins were identified as lead structures against drought stress in crops starting from protein docking studies of a sulfonamide lead structure, followed by in-depth SAR studies. Optimized five to six step synthetic approaches via substituted amino oxo-tetrahydroquinolines and amino oxo-indolines as essential intermediates gave access to the envisaged oxo-tetrahydroquinolinyl and oxindolinyl sulfonamides. Whilst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Along with plant hormone ABA 1 , we have tested lunularic acid 2 as reference in our greenhouse trials (Table 2, entries 29, 30). In line with results from earlier studies ABA 1 showed good effects in all three crops, [34–36] whereas lunularic acid 2 only showed efficacy against drought stress in wheat and canola. In good accordance with the strong performance of prototype 5 a carrying a p ‐methoxyphenyl substituent (entry 1, Table 2) other 2,3‐dihydro‐1‐benzofuran‐4‐carboxylates 5 carrying alkoxy, phenoxy or acyloxy groups at position R 7 in the phenyl moiety showed good efficacy against drought stress ( 5 h – l , entries 8–12, Table 2) with 5 k (R 7 =OAc, Table 2, entry 11) showing particularly promising results in wheat.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Along with plant hormone ABA 1 , we have tested lunularic acid 2 as reference in our greenhouse trials (Table 2, entries 29, 30). In line with results from earlier studies ABA 1 showed good effects in all three crops, [34–36] whereas lunularic acid 2 only showed efficacy against drought stress in wheat and canola. In good accordance with the strong performance of prototype 5 a carrying a p ‐methoxyphenyl substituent (entry 1, Table 2) other 2,3‐dihydro‐1‐benzofuran‐4‐carboxylates 5 carrying alkoxy, phenoxy or acyloxy groups at position R 7 in the phenyl moiety showed good efficacy against drought stress ( 5 h – l , entries 8–12, Table 2) with 5 k (R 7 =OAc, Table 2, entry 11) showing particularly promising results in wheat.…”
Section: Resultssupporting
confidence: 90%
“…Whilst our SAR-studies in the field of synthetic agonists of abscisic acid 1 were based on a combination of receptor docking studies using results from protein crystallography, in vitro measurements of target affinity and results from in vivo greenhouse trials, [34][35][36] we had to rely on in vivo test results only when investigating the SAR of dihydrobenzofuran carboxylates since the potential mode of action of lunularic acid in higher plants has not been elucidated so far. Hence, we decided to evaluate the four main diversity points carefully, i) the impact of changes in the substitution pattern of the phenyl moiety, ii) additional substituents in the salicylate core motif, iii) substituents and protecting groups of the free hydroxyl group, and iv) functionalization of the carboxylic acid group.…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Oxindoles (1,3-dihydro-2H-indol-2-ones) are a privileged structural motif, which not only occur widely in bioactive natural products and pharmaceuticals [1][2][3][4][5][6] but are also used as synthetic intermediates for various organic transformations [7][8][9][10][11][12]. Many synthetic strategies have been established to access this skeleton, including the oxidation of indoles, [13][14][15] transition metal-catalyzed Heck-type reactions of acrylamides, [16][17][18][19][20][21][22][23][24] metalcatalyzed cyclization of o-haloacetanilides, [25][26][27][28][29] reductive desulfurization of 3-methylthiooxindoles, 30,31 double C-H oxidative coupling of functionalized acetanilides, [32][33][34][35][36][37][38][39] the C-H oxidative radical coupling of acrylanilides, [40][41][42][43] and so on (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…A literature survey revealed that the installation/construction of oxindole and dihydroquinolin-2-one cores mostly rely on ring-closing strategies that usually depend on methodologies catalyzed by transition metals that require long reaction times (Scheme 1 A). [25][26][27][28][29][30][31][32][33][34][35][36][37][38] For example, oxindoles can be prepared from N-aryl acrylamides, through hydroarylation, where the latest methodologies involving reductive Heck coupling reactions are applied. [27,28] Other hydroarylation methodologies involve the use of organometallic catalysts with Pd, Ru, Ni and Ir [29][30][31][32] , where it may be necessary to use an inert atmosphere and may also require a long reaction time.…”
Section: Introductionmentioning
confidence: 99%